2015
DOI: 10.1007/s11099-015-0146-x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and antioxidant responses to drought during sugarcane ripening

Abstract: Water deficit is an important exogenous factor that enhances the influx of sucrose into sugarcane (Saccharum spp.) stem internodes during ripening, when photosynthetic ability in supplying sinks is essential. The aim of this study was to test the hypothesis that drought tolerance in sugarcane is associated with an effective antioxidant protection during the ripening phase, which might maintain a favorable redox balance in chloroplasts and protect photosynthesis under drought conditions. Two commercial sugarcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…In addition, ETR/PN increased due to the increase previously described to NPQ, suggesting that occurred lower electron transfer to CO2 fixation, with consequent use of these electrons to photorespiration and other metabolic processes . Similar behavior was reported to EXC in Saccharum spp plants (Sales et al, 2015) and Jatropha curcas (Silva et al, 2015). Rivas et al (2016) studying two cultivars of V. unguiculata, 'Pingo de Ouro 1-2' and Santo Inácio, found reductions for NPQ in 80% and 200%, respectively, after 10 days of irrigation suspension.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, ETR/PN increased due to the increase previously described to NPQ, suggesting that occurred lower electron transfer to CO2 fixation, with consequent use of these electrons to photorespiration and other metabolic processes . Similar behavior was reported to EXC in Saccharum spp plants (Sales et al, 2015) and Jatropha curcas (Silva et al, 2015). Rivas et al (2016) studying two cultivars of V. unguiculata, 'Pingo de Ouro 1-2' and Santo Inácio, found reductions for NPQ in 80% and 200%, respectively, after 10 days of irrigation suspension.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, a correlation between water stress tolerance and lower levels of lipid peroxidation was reported (Cia et al, 2012; Sales et al, 2015). According to Abbas et al (2014) lipid peroxidation may be a good parameter to identify water stress tolerant sugarcane varieties.…”
Section: Lipid Peroxidationmentioning
confidence: 96%
“…The superoxide dismutase (SOD) activity plays the first line of enzymatic ROS scavenging, catalyzing the conversion of O2- into H 2 O 2 within the cell. In sugarcane, SOD activity is genotype-dependent and is also modulated by water stress (Hemaprabha et al, 2004; Jain et al, 2015; Sales et al, 2015; dos Santos et al, 2015; dos Santos and de Almeida Silva, 2015). Moreover, (Jangpromma et al, 2012) showed that sugarcane cultivars classified as drought-tolerant exhibit higher levels of SOD activity under water deficit conditions.…”
Section: Ros Accumulation and Antioxidant Activitymentioning
confidence: 99%
“…Jackson et al (2015) compararam a variação genética de cinco genótipos de cana-de-açúcar em relação à eficiência da transpiração foliar. Sales et al (2015) testaram a hipótese de que a tolerância à seca em cana-de-açúcar está associada a uma resposta metabólica (antioxidante) eficaz durante a fase de amadurecimento, o que permite manter alta as taxas de fotossíntese durante a seca. Simões et al (2015) avaliaram as variáveis fisiológicas (transpiração e condutância estomática) da cana-de-açúcar em função do sistema de irrigação.…”
Section: Introductionunclassified